Aplikasi Pupuk Organik Cair (POC) dan Pupuk NPK Terhadap Produksi Kacang Panjang (Vigna sinensis L.) - Siti Khairani; Hardianti Putri Sari; Zul Fadhly (JURNAL AGROPLASMA, 2026)
Long bean is an important vegetable commodity whose production has been continuously declining due to the excessive and prolonged use of inorganic fertilizers. This study aimed to determine the effect of Liquid Organic Fertilizer (LOF) NASA and NPK fertilizer application, as well as their interaction, on the growth and production of long bean (Vigna sinensis L.). The study was conducted at the experimental field of Sei Semayang, Deli Serdang Regency, North Sumatra, at an altitude of ±30 meters above sea level, from September to December 2025. The method used was a Factorial Randomized Block Design with two factors and three replications. The first factor was the concentration of LOF NASA (0, 2, 4, and 6 ml/liter) and the second factor was the dose of NPK fertilizer (0, 200, 300, and 400 kg/ha). The results showed that LOF NASA and NPK fertilizer treatments each had a significant effect on all observed parameters, with a positive linear relationship at each increasing dose. The best LOF NASA concentration was obtained at 6 ml/liter (C3), which produced a pod length of 60.10 cm, pod weight per plant of 321.38 g, number of pods of 12.30 pods, and plot production of 4.65 kg. The best NPK fertilizer dose was obtained at 400 kg/ha (N3), which produced a pod length of 62.29 cm, pod weight per plant of 346.53 g, number of pods of 12.88 pods, and plot production of 4.87 kg. However, the interaction between LOF NASA and NPK fertilizer did not significantly affect all observed parameters. Keywords : long bean, LOF, NPK fertilizer